Pembelajaran Akidah Akhlak Sebagai Pendidikan Karakter Menghargai Peserta Didik - Yafi, Salman; Kustati, Martin; Gusmirawati (MSJ : Majority Science Journal, 2023)
The biggest challenge for education in Indonesia today is the moral degradation that occurs among students. To anticipate this, character education is advanced as one of the right alternative solutions. In addition, learning akidah akhlak is also a subject that has a close relationship with character education and moral improvement of students. The purpose of this study is to describe the learning of moral creed as appreciative character education at MTsN 5 Padang City. This type of research is based on field research, namely research conducted by going directly to the field, namely at Madrasah Tsanawiyah Negeri 5 Kota Padang with a qualitative descriptive approach. The result of this research is that the character of respect has an important value for students and also for the teacher himself. Besides making the class more active, students' confidence becomes more confident in expressing their opinions. In the independent curriculum, the application of respect character values is easier to do with the implementation of problem-based and project-based learning models. With group work, students can directly apply the character of respect apart from getting the theory given by the teacher. Not to forget, the teacher must also conduct an evaluation on the emotional realm so that the application of the character of respect is more embedded in the chest of participants in the curriculum.